Penggunaan Media Puzzle Angka Dalam Mengembangkan Kemampuan Berhitung Permulaan Anak di SDN 101769 Tembung - Susanti, Susanti; Basri, Muhammad; Zunidar, Zunidar (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2025)
This research aims to describe the use of number puzzle media in developing early counting skills in first-grade students at SDN 101769 Tembung, as well as to describe the advantages and disadvantages of using number puzzle media in developing early counting skills in first-grade students at SDN 101769 Tembung. This type of research uses qualitative research with a descriptive method. The data collection techniques used are observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. Next, the technique for verifying data validity uses Triangulation Technique. From the research results, it shows that the use of number puzzle media for first-grade students at SDN 101769 Tembung, conducted gradually according to the correct procedures, has proven to be able to develop initial counting skills. The unique and attractive form of the number puzzle media is an advantage of the number puzzle media because it can develop children's enthusiasm and spirit in learning basic counting. The disadvantage of using number puzzle media is that the learning process with number puzzle media requires more time to complete, and the number puzzle media itself emphasizes the visual sense. (visual).